If x + y = 1, then the value of x3 + y3 + 3xy is
(1) 1 (2) 0
(3) 2 (4) 3
Answers
Answered by
20
x+y = 1
(x+y)³ = (1)³
x³ + y³ + 3xy(x+y) = 1
x³ + y³ + 3xy(1) = 1
x³ + y³ + 3xy = 1
(a+b)³ = a³ + b³ +3ab(a+b)
(x+y)³ = (1)³
x³ + y³ + 3xy(x+y) = 1
x³ + y³ + 3xy(1) = 1
x³ + y³ + 3xy = 1
(a+b)³ = a³ + b³ +3ab(a+b)
Answered by
6
We know that this problem can be easily solved by the help of identities
Given :
![x + y = 1 \\ \\ x + y = 1 \\ \\](https://tex.z-dn.net/?f=x+%2B+y+%3D+1+%5C%5C+%5C%5C+)
Find:
![{x}^{3} + {y}^{3} + 3xy\\ {x}^{3} + {y}^{3} + 3xy\\](https://tex.z-dn.net/?f=+%7Bx%7D%5E%7B3%7D+%2B+%7By%7D%5E%7B3%7D+%2B+3xy%5C%5C+)
We also know that for that we had to cube the expression
Take cube both sides of given expression
![{(x + y)}^{3} = ( {1)}^{3} \\ \\ open \: identity \\ \\ {x}^{3} + {y}^{3} + 3xy(x + y) = 1 \\ \\ from \: given \: expression \:put \: x + y = 1 \\ \\ \\ {x}^{3} + {y}^{3} + 3xy(1) = 1 \\ \\ {x}^{3} + {y}^{3} + 3xy = 1 \\ \\ {(x + y)}^{3} = ( {1)}^{3} \\ \\ open \: identity \\ \\ {x}^{3} + {y}^{3} + 3xy(x + y) = 1 \\ \\ from \: given \: expression \:put \: x + y = 1 \\ \\ \\ {x}^{3} + {y}^{3} + 3xy(1) = 1 \\ \\ {x}^{3} + {y}^{3} + 3xy = 1 \\ \\](https://tex.z-dn.net/?f=+%7B%28x+%2B+y%29%7D%5E%7B3%7D+%3D+%28+%7B1%29%7D%5E%7B3%7D+%5C%5C+%5C%5C+open+%5C%3A+identity+%5C%5C+%5C%5C+%7Bx%7D%5E%7B3%7D+%2B+%7By%7D%5E%7B3%7D+%2B+3xy%28x+%2B+y%29+%3D+1+%5C%5C+%5C%5C+from+%5C%3A+given+%5C%3A+expression+%5C%3Aput+%5C%3A+x+%2B+y+%3D+1+%5C%5C+%5C%5C+%5C%5C+%7Bx%7D%5E%7B3%7D+%2B+%7By%7D%5E%7B3%7D+%2B+3xy%281%29+%3D+1+%5C%5C+%5C%5C+%7Bx%7D%5E%7B3%7D+%2B+%7By%7D%5E%7B3%7D+%2B+3xy+%3D+1+%5C%5C+%5C%5C+)
Thus,Option (1) is correct.
Hope it helps you.
Given :
Find:
We also know that for that we had to cube the expression
Take cube both sides of given expression
Thus,Option (1) is correct.
Hope it helps you.
Similar questions